O pior controle glicêmico no diabetes e a deficiência de vitamina D prejudicam a velocidade de caminhada em pessoas idosas a longo prazo? - Luiz, Mariane Marques (Universidade Federal de São Carlos, 2024)
The mobility decline, evidenced by reduced walking speed (WS), is an important indicator of general health status and risk of adverse outcomes in older people. Although multifactorial, recent literature suggests that endocrine, metabolic, and nutritional diseases, such as diabetes and vitamin D deficiency, are factors associated with WS decline. However, no study has analyzed this association from the perspective of glycemic control of diabetes, measured by glycated hemoglobin (HbA1c) levels, and there are still controversies regarding the longitudinal association between vitamin D deficiency and slowness. Thus, the three objectives of this thesis were to verify if: 1) glycemic control status in diabetes is a risk factor for WS decline trajectories in older adults over eight years of follow-up; 2) the previous mobility condition of these individuals modifies these trajectories; and 3) vitamin D insufficiency and deficiency are risk factors for incidence of slowness in older adults over six years of follow-up. Two studies were conducted with participants aged 60 or older from the English Longitudinal Study of Ageing (ELSA). In study 1, a trajectory analysis, a sample of 3,202 participants and another of 2,126 participants without slowness (WS > 0.8 m/s) at baseline met the first and second objectives, respectively. At baseline and after four and eight years of follow-up, all participants were classified regarding glycemic control status as "without diabetes" (WD) (self-reported no diabetes and HbA1c < 6.5%), "adequate glycemic control" (AGC) (self-reported diabetes and HbA1c ≥ 6.5% and < 7.0%), and "poorer glycemic control" (PGC) (self-reported diabetes and HbA1c ≥ 7.0%). Generalized linear mixed models controlled for sociodemographic, behavioral, and clinical characteristics were used to analyze WS trajectories in m/s according to glycemic control status over the eight years of follow-up. Results showed the annual WS decline was more pronounced in individuals with PGC (-0.015 m/s) and AGC (-0.011 m/s) compared to WD individuals, corresponding to a total decline of -0.160 m/s and -0.130 m/s, respectively, during eight-year of follow-up. Among participants without slowness at baseline, only those with PGC had a significant WS decline when compared to the WD group, corresponding to -0.014 m/s per year, and -0.222 m/s over the eight years of follow-up. In study 2, an incidence analysis, a sample of 2,815 individuals without slowness at baseline (WS > 0.8 m/s) met the third objective. The vitamin D levels of the participants were measured by serum levels of 25-hydroxyvitamin D [25(OH)D] and classified as sufficiency (> 50 nmol/L), insufficiency (> 30 to ≤ 50 nmol/L), and deficiency (≤ 30 nmol/L). With four and six years of follow-up, WS was reassessed to identify incident cases of slowness (WS ≤ 0.8 m/s). Incidence densities of slowness according to serum levels of 25(OH)D were calculated, and a Poisson model controlled for sociodemographic, behavioral, and clinical characteristics was used to analyze the association between serum levels of 25(OH)D and the risk of incidence of slowness. Results demonstrated that serum 25(OH)D deficiency increased the incidence density of slowness (90.7/1000 person/years) when compared to serum 25(OH)D sufficiency (67,4/1000 person/year) and increased the risk of incidence of slowness by 22%. Serum 25(OH)D insufficiency did not present as a risk factor for the incidence of slowness. Thus, our results demonstrate that poor glycemic control and vitamin D deficiency are risk factors for mobility limitation in older people. These findings allow early identification of individuals at higher risk of WS decline and reinforce the need for assertive strategies in managing glycemic control and vitamin D levels, especially in older adults, to prevent complications of these conditions, particularly in mobility.
Does poor glycemic control in diabetes and vitamin D deficiency impair walking speed in older people in the long term?
Keywords: Controle glicêmico; Complicações do diabetes; Hiperglicemia; Limitação da mobilidade; Velocidade de caminhada; Deficiência de vitamina D; Glycemic control; Complications of diabetes; Hyperglycemia; Mobility limitation; Walking speed; Vitamin D deficiency; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL